(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
The OCEM Journal of Management, Technology, and Social Sciences introduces a comprehensive model for journal editorial pages to augment scholarly publications’ overall quality and impact. This model incorporates essential elements, including the composition of the editorial board, review processes, communication strategies, and fostering engagement with authors and readers. Embracing a systematic approach, the model strives to optimize editorial pages, catering to both traditional and online journal formats. The references to established literature and scholarly works are meticulously included, offering a robust foundation for the outlined framework to substantiate the proposed model. This section provides a brief overview of the journal, setting the stage for the valuable content and discussions that follow. The OCEM Journal of Management, Technology & Social Sciences is a multidisciplinary, peer-reviewed journal that provides a platform for the integration of management, technology, and social sciences. The journal is committed to publishing high-impact research articles that contribute to the advancement of these fields. With a focus on fostering engagement and communication, the journal’s comprehensive model for journal editorial pages aims to enhance the quality and relevance of scholarly publications. This structured abstract serves as a guide for authors, highlighting the journal’s emphasis on rigorous review processes, diverse content, and a systematic approach to scholarly exchange.